Penerapan Model Pembelajaran Problem Base Learning (PBL) untuk Meningkatkan Hasil Belajar IPAS Materi Kearifan Lokal di Kelas 4 SD Muhammadiyah 4 Kota Batu - Tria Rosiana; Reni Mega Sari; Nurwidodo Nurwidodo (Universitas Islam Lamongan, 2023)
The success of science learning in Indonesia is very low. Science education in schools aims to enable students to play an active role in learning about themselves and their natural environment and apply them in everyday life. The cause of the lack of optimal science learning is that teaching methods are still traditional, teachers give lectures, explain in front of students during class, and actively and proactively ask questions in class. As a result, the learning process is mastered only by the teacher and a small part of students. This research is a Classroom Action Research (PTK) that can be followed up to improve learning in the classroom by applying the PBL learning method, in science subjects with the subject of local wisdom. The subjects of the study were students of Kela IV SD Muhammadiyah 4 Kota Batu in the odd semester of the 2022/2023 academic year. Based on the results of research conducted at SDN Muhammadiyah 4 Batu City, it can be concluded that the application of problem-based learning is an attractive method for students. PBL encourages students to think critically, identify, analyze, and solve problems in everyday life. Help students understand topics more easily and accurately. This is reflected in the increase in the value of student learning outcomes in the initial condition until cycle II reached 56%, especially cognitive learning outcomes. Implementing group learning can improve cognitive learning outcomes. Classroom action research entitled Application of the Problem Base Learning (PBL) Learning Model to Improve Science Learning Outcomes of Local Wisdom Material in Grade 4 SD Muhammadiyah 4 Kota Batu. The results obtained from the study are an increase in student learning outcomes which can be seen from the initial condition of the completeness of student learning outcomes as much as 44%, cycle I 76%, and cycle II 100%.